E-learning: Novos Rumos em Educação e Treinamento - Neide Santos, Cristiane da Costa Pimentel (Cadernos do IME - Série Informática, 2013)
The paper discusses new ways for distance learning, outlining the e-learning idea.  E-learning try to minimize some difficulties found in the traditional teaching and learning process, offering clear and objective self-instruction resources and favoring the implementation of comprehensive and interactive software, with easy operation in graphic environments with simple interface. It also presents the requirements, user cases and scenarios of an interactive site for e-learning activities system, called 2Learn.